Food entrainment: major and recent findings - Carneiro, Breno T.; Araujo, John F. (Frontiers in Behavioral Neuroscience, 2012)
Mammals exhibit daily anticipatory activity to cycles of food availability. Studies on such food anticipatory activity (FAA) have been conducted mainly in nocturnal rodents. They have identified FAA as the behavioral output of a food entrained oscillator (FEO), separate of the known light entrained oscillator (LEO) located in the suprachiasmatic nucleus of hypothalamus (SCN). Here we briefly review the main characteristics of FAA. Also, we present results on four topics of food anticipation: (1) possible input signals to FEO, (2) FEO substrate, (3) the importance of canonical clock genes for FAA and (4) potential practical applications of scheduled feeding. This mini review is intended to introduce the subject of food entrainment to those unfamiliar with it but also present them with relevant new findings on the issue.